Contraception in Malignancies: Kontrasepsi pada Keganasan - Tricia D Anggraeni; Yosep Sutandar (Indonesian Journal of Obstetrics and Gynecology, 2014)
Along with the development of cancer diagnosis and treatment, the life expectancy of women in reproductive age who suffer from cancer are also higher. Women with cancer still have the possibility to be pregnant and have a child during or after completion of therapy. Taking this into consideration, the guideline for contraception in special circumstances like this is needed. After reviewing the safety and effectiveness of contraceptive methods available for women with cancer, The Society of Family Planning urged not to use combination hormonal contraceptives (estrogen and progestin). Hormonal contraceptive use in cancer patients may increase the risk of venous thromboembolism (Level A). T380A IUD, which has a high effectiveness, reversible, long-term, and hormone-free contraception should be considered as the primary choice in patients with breast cancer (Level A). In women who received tamoxifen therapy, the use of IUD containing Levonorgestrel can be considered as a second choice (Level B) because it can decrease the proliferation endometrium. Women with anemia due to chemotherapy may be given contraceptive containing progestin (Level A). Women with osteopenia or osteoporosis after chemotherapy should avoid progestin contraceptive injection (Level A). Currently, there are no data to evaluate the risk of venous thromboembolism in progestin contraceptive use. Further information is also needed to determine the effect of the use of IUD that contains Levonorgestrel against breast cancer recurrence and the effect of hormonal contraceptives on breast cancer in women who received chest wall radiotherapy. Keywords: cancer, contraception, malignancy